Analysis of the risk factors for secondary hemorrhage after abdominal surgery - Pang, Tianshu; Wu, Zhengrong; Zeng, Hongfen; Zhang, Xiangyu; Hu, Mengya; Cao, Liping (Frontiers in Surgery, 2023)
Introduction This study aimed to conduct a clinical review and analysis to recommend options for the prevention and treatment of postoperative hemorrhage. Patients and Methods A total of 138 patients who experienced postoperative hemorrhage after abdominal surgery in the period between January 2015 and December 2020 at the Sir Run Run Shaw Hospital, affiliated to Zhejiang University School of Medicine, participated in this study. They were divided into a group with primary bleeding only and a secondary bleeding group. Univariate and multivariate statistical analyses were performed, followed by plotting of cumulative hazard and survival curves for the two groups. Results The main factors of interest found to be associated with secondary hemorrhage were duration of the operation, the time of the first bleeding incident, intervention time, performance of combined organ resection, use of surgical intervention, occurrence of abdominal infection, admission to the intensive care unit (ICU), postoperative length of stay, and total hospitalization expenses. Among these, a long operative duration (>5 h) and an extended intervention time (>5 h) were identified as independent predictors of risk of secondary hemorrhage. Conclusions Secondary hemorrhage after abdominal surgery is mainly associated with subjective human factors, and it is an important cause of poor prognosis and even death. Proper reductions in operation time and implementation of a quick response to bleeding are the key factors in tackling bleeding. Further reduction in the rates of postoperative hemorrhage and mortality will require a concerted effort by surgeons in terms of both intraoperative surgical techniques and postoperative management.